Preparation method of contraceptive implant medicine core

By using extrusion method instead of mold pressing method in the preparation of contraceptive implant cores, the problem of waste edge fragments and raw materials is solved, and the preparation of high-quality drug cores and effective contraceptive effects are achieved.

CN119488432APending Publication Date: 2025-02-21SHANGHAI DAHUA PHARM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411634145.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the existing method of preparing contraceptive implant cores, the mold pressing method leads to the generation of waste edge fragments and waste of raw materials.

Method used

The extrusion method is used instead of the mold pressing method, and the glue is extruded and kneaded by screws to obtain the core rod, and the core is quickly vulcanized. After cutting and trimming, the finished core is obtained.

Benefits of technology

It greatly reduces the generation of waste edge fragments, avoids the loss and waste of raw materials, and ensures the quality of the medicine core and the effect of contraceptives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136724440000061
    Figure BDA0005136724440000061
  • Figure BDA0005136724440000071
    Figure BDA0005136724440000071
Patent Text Reader

Abstract

The invention relates to the technical field of contraception implant production, and particularly discloses a preparation method of a contraception implant medicine core, which comprises the following steps: (1) weighing a component A and a component B, and respectively premixing; (2) mixing the component A and the component B to obtain a rubber compound; (3) placing the rubber compound in an extruder, and extruding the mixture through screw extrusion to obtain an extruded flux-cored rod; (4) vulcanizing the extruded flux core rod, cutting, cooling, and trimming to obtain a finished product flux core; the component A comprises levonorgestrel, LS-4100 silicone rubber, white carbon black, a platinum complex and methyl butynol; and the component B comprises levonorgestrel, LS-4100 silicone rubber, white carbon black, hydrogen-containing silicone oil and a mixed additive. In the actual application process of the preparation method, it is guaranteed that the contraceptive implant medicine core with good quality is obtained, loss and waste of raw materials for preparing the medicine core can be reduced, and the whole medicine core has a good application effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of contraceptive implant production, and more specifically, to a method for preparing a contraceptive implant core. Background Art

[0002] Subcutaneous implant contraceptive method is a kind of sustained-release contraceptive method. It uses high molecular compound (usually silica gel) as release carrier, puts contraceptive (usually progesterone) in it, cuts a 2 cm small hole on the arm of women of childbearing age, and releases progesterone slowly and continuously into the body. Progesterone can achieve the contraceptive effect by inhibiting ovulation, increasing the thickness of cervical mucus, and thinning the endometrium. The effectiveness of subcutaneous implant contraceptive is as high as 99.9%, and the contraceptive effect can generally last for about 3 years.

[0003] Contraceptive implants are usually composed of a medicine core and a silicone tube. First, use medical adhesive to seal one end of the silicone, then put the medicine core into the silicone tube, and finally use medical adhesive to seal the other end of the silicone tube to obtain the contraceptive implant. The invention patent with the patent publication number CN 113413358A discloses a method for preparing a contraceptive implant core, which includes the following steps: weighing a group A component and a group B component, wherein the weight ratio of the group A component to the group B component is 1:1; mixing the group A component and the group B component to obtain a mixed rubber; filling the mixed rubber into a mold, vulcanizing the mold, and obtaining a crude core; cooling the crude core, trimming the core, and obtaining a finished core; the group A component includes 98-102 parts of levonorgestrel, 93-97 parts of LS-4100 silicone rubber, 3-5 parts of white carbon black, and 0.5-1.5 parts of a platinum complex; the group B component includes 98-102 parts of levonorgestrel, 93-97 parts of LS-4100 silicone rubber, 3-5 parts of white carbon black, and 0.5-1.5 parts of hydrogenated silicone oil. The above preparation method has a simple process, high precision, a high core yield, and a good quality of the prepared core.

[0004] With respect to the above-mentioned related technologies, the inventors believe that although the above-mentioned mold pressing method for preparing the medicine core can obtain medicine cores of better quality, the mold pressing method will produce waste scraps each time it is produced, and waste scraps will also be produced during the trimming process of the obtained rough medicine core, thus causing a large amount of waste of raw materials. It is currently urgent to propose a solution to solve the above-mentioned technical problems. Summary of the invention

[0005] In order to ensure that a good quality drug core is obtained and to reduce the loss and waste of raw materials used in drug core preparation during drug core preparation, the present application provides a method for preparing a contraceptive implant drug core.

[0006] The present application provides a method for preparing a contraceptive implant core, which adopts the following technical solution: A method for preparing a contraceptive implant core comprises the following steps: (1) Weigh the components of Group A and Group B and premix them separately; (2) mixing the components of group A and group B to obtain a rubber mixture; (3) placing the rubber mixture in an extruder and extruding the mixture through a screw to obtain an extruded core rod; (4) vulcanizing the extruded core rod, cutting, cooling, and trimming to obtain a finished core rod; The group A components include the following raw materials: levonorgestrel, LS-4100 silicone rubber, white carbon black, platinum complex, methyl butynol; The group B components include the following raw materials: levonorgestrel, LS-4100 silicone rubber, white carbon black, hydrogen-containing silicone oil, and a mixing aid; the mixing aid is composed of raw materials including microcrystalline cellulose and magnesium stearate, and the weight ratio of microcrystalline cellulose to magnesium stearate is (8-15):1.

[0007] By adopting the above technical scheme, in the preparation of the contraceptive implant core, the extrusion method is used instead of the mold pressing method, which can greatly reduce the generation of waste and scraps, thereby avoiding the loss and waste of raw materials in the preparation; and in order to ensure that the contraceptive implant core obtained by the extrusion method has a better quality, methylbutynol is used in the group A component used in the preparation, which can inhibit the vulcanization of the product within a certain period of time, so that the group A component and the group B component present a fluid state that is easy to extrude after mixing, and at the same time, a mixed auxiliary agent containing microcrystalline cellulose and magnesium stearate is used in the group B component, through the excellent shaping effect brought by the compounding of microcrystalline cellulose and magnesium stearate, and the uniform and stable combination of the raw materials can be maintained during the extrusion process, thereby obtaining a better extrusion shape; after obtaining the extruded core rod, a rapid vulcanization treatment is immediately performed to produce a milky white cylindrical core product, which is then cut according to production requirements, and the finished core can be obtained after simple trimming. In actual application, the above preparation method can not only ensure the acquisition of contraceptive implant cores with better quality, but also reduce the loss and waste of raw materials in the preparation of the cores, and has a better application effect as a whole.

[0008] Preferably, the weight ratio of microcrystalline cellulose to magnesium stearate is 12:1.

[0009] By adopting the above technical scheme, microcrystalline cellulose can bring about a filling effect in the mixing system of group A components and group B components, improve the fluidity of the system, and also serve as a sustained-release carrier and bring about a skeleton support effect; magnesium stearate can make the mixing system of group A components and group B components have better fluidity, and can be adsorbed on the surface of the material to form a lubricating film; and when microcrystalline cellulose and magnesium stearate are used in combination according to the above proportion, the skeleton membrane structure formed by the compounding of the two is relatively uniform, and it can exert a relatively excellent corresponding effect when interspersed between the raw materials, thereby obtaining a contraceptive implant core with better quality, and making the entire preparation operation process more stable, and the better molding effect can ensure that less waste and fragments are generated by subsequent trimming, which has an excellent promoting effect on reducing the loss and waste of raw materials in the preparation of the core.

[0010] Preferably, the mass proportion of the methylbutynol in the group A components is 0.5-1%.

[0011] By adopting the above technical solution, the methylbutynol with the above mass proportion can exert excellent corresponding effects during the application process. While inhibiting the vulcanization of the product, it can also better cooperate with the mixing additives to regulate the extrusion state and ensure the stability of the preparation process.

[0012] Preferably, the mass proportion of the mixing aid in the components of group B is 3-5%.

[0013] By adopting the above technical scheme, the mixed auxiliary agents with the above mass proportion can exert excellent corresponding effects during the application process, and show stable synergistic effects with methylbutynol, and can obtain a better extrusion morphology during the preparation process, thereby ensuring that a contraceptive implant core with better quality is obtained while reducing the loss and waste of raw materials in the preparation of the core.

[0014] Preferably, in step (2), the distance between the rollers during mixing is 0.1-0.2 mm, and the mixing time is 2-3 min.

[0015] By adopting the above technical solution, during mixing, the selection of the above required parameters can ensure that the components of Group A and Group B are fully mixed, and the methylbutynol and mixing aids contained therein can also play a stable role in the subsequent operations after the mixing is completed.

[0016] Preferably, in step (3), the extrusion speed of the extruder is 5-12 r / min, and the extrusion port temperature of the extruder is 120-140°C.

[0017] By adopting the above technical scheme and selecting the above extrusion speed and extrusion port temperature, a better extrusion morphology can be obtained, which effectively avoids a large amount of waste scraps caused by subsequent trimming due to poor molding state, and also can obtain a contraceptive implant core with better quality, making the application of the entire preparation method more excellent and stable.

[0018] Preferably, in step (4), a drying oven with a temperature of 275-285° C. and a time of 2-5 min is used during the vulcanization process.

[0019] By adopting the above technical scheme and selecting the above temperature and time, the extruded core rod can be vulcanized quickly and fully, so that a contraceptive implant core with good quality can be obtained; at the same time, the rapid molding at the above temperature is also suitable for the extrusion shape of the core rod, avoiding deformation of the core rod after vulcanization due to a long vulcanization time, thereby significantly reducing the waste and scraps generated by trimming, and ensuring the excellent stability of the entire preparation operation.

[0020] Preferably, in step (4), the finished drug core has a length of 43 mm, a diameter of 2.1±0.01 mm, and a weight of 145-157 mg.

[0021] By adopting the above technical solution, the finished drug core produced has a standard size and contains sufficient medicine. The contraceptive implant produced using the drug core of the present application can effectively prevent pregnancy for 48 months after implantation, and the annual contraceptive failure rate is less than 1%.

[0022] Preferably, the weight ratio of the group A components to the group B components is 1:1.

[0023] By adopting the above technical solution, after mixing the group A components and the group B components in the above weight ratio, the raw materials contained therein can be fully mixed and dispersed, and can be easily and quickly vulcanized, thereby obtaining a contraceptive implant core with better quality and stability.

[0024] In summary, this application has the following beneficial effects: The present application uses extrusion instead of mold pressing, which can greatly reduce the generation of waste and scraps. At the same time, methylbutynol is used in the group A component and a mixed auxiliary agent containing microcrystalline cellulose and magnesium stearate is used in the group B component, which can ensure that the mixed group A component and group B component obtain a better extrusion shape during the extrusion molding process, which is beneficial to reduce the waste and scraps generated by trimming and ensure that a contraceptive implant core with better quality is obtained, and the overall application effect is better. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0026] The raw materials used in the examples and comparative examples of the present application are commercially available except for the following special instructions: Levonorgestrel was obtained from Qinhuangdao Zizhu Pharmaceutical Co., Ltd.; LS-4100 silicone rubber is medical grade LS-4100 addition silicone rubber; White carbon black from EVONUK (Evonik Group), brand: R106; The platinum complex was obtained from Hubei Langbowan Biopharmaceutical Co., Ltd. The CAS number is 68478-92-2, and the content is 98%; Hydrogenated silicone oil was obtained from Jinan Longcheng Organic Silicone Co., Ltd., brand: Gao 202; Microcrystalline cellulose was purchased from Xi'an Hongyao Pharmaceutical Excipients Co., Ltd., pharmaceutical grade; Magnesium stearate was purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd., model CP2020. Example

[0027] Example 1 A method for preparing a contraceptive implant core comprises the following steps: (1) Weigh the components of Group A and Group B and premix them separately; (2) mixing the components of group A and group B, wherein the distance between the rollers during mixing is 0.15 mm and the mixing time is 2.5 min to obtain a mixed rubber; (3) placing the rubber mixture in an extruder, extruding the mixture through a screw, the extrusion speed of the extruder being 8.5 r / min, the extrusion port temperature of the extruder being 130° C., and obtaining an extruded core rod; (4) The extruded core rod is vulcanized in a drying oven at 280° C. for 3.5 min. After cutting, cooling, and trimming, a finished core rod is obtained.

[0028] The group A component is composed of the following raw materials in percentage by mass: 50% levonorgestrel, 47% LS-4100 silicone rubber, 2% white carbon black, 0.25% platinum complex, and 0.75% methyl butynol; Group B is composed of the following raw materials in percentage by mass: 48.5% levonorgestrel, 45% LS-4100 silicone rubber, 2% white carbon black, 0.5% hydrogenated silicone oil, and 4% mixing aid; The mixing aid is composed of microcrystalline cellulose and magnesium stearate, and the weight ratio of the microcrystalline cellulose to the magnesium stearate is 12:1.

[0029] Note: In step (4), if the length of the finished drug core is 43 mm, the diameter is 2.1 ± 0.01 mm, and the weight is 145-157 mg, it is considered qualified, otherwise, it is unqualified. The weight ratio of Group A components to Group B components is 1:1.

[0030] Example 2 A method for preparing a contraceptive implant core, which is different from Example 1 in that the weight ratio of microcrystalline cellulose to magnesium stearate is 11.5:1.

[0031] Example 3 A method for preparing a contraceptive implant core, which is different from Example 1 in that the weight ratio of microcrystalline cellulose to magnesium stearate is 8:1.

[0032] Example 4 A method for preparing a contraceptive implant core, which is different from Example 1 in that the weight ratio of microcrystalline cellulose to magnesium stearate is 15:1.

[0033] Example 5 A method for preparing a contraceptive implant core is different from Example 1 in that the total raw material mass of Group A components remains unchanged, the mass proportion of methylbutynol in Group A components is adjusted to 0.5%, and the ratios of other raw materials to each other remain unchanged.

[0034] Example 6 A method for preparing a contraceptive implant core is different from that of Example 1 in that the total mass of raw materials in Group A components remains unchanged, the mass proportion of methylbutynol in Group A components is 1%, and the proportions of other raw materials to each other remain unchanged.

[0035] Example 7 A method for preparing a contraceptive implant core is different from Example 1 in that the total raw material mass of Group B components remains unchanged, the mass proportion of the mixing auxiliary in Group B components is 3%, and the proportions of other raw materials to each other remain unchanged.

[0036] Example 8 A method for preparing a contraceptive implant core is different from Example 1 in that the total raw material mass of Group B components remains unchanged, the mass proportion of the mixing auxiliary in Group B components is 5%, and the proportions of other raw materials to each other remain unchanged.

[0037] Example 9 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (2), the distance between the rollers during mixing is 0.1 mm, and the mixing time is 2 min.

[0038] Example 10 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (2), the distance between the rollers during mixing is 0.2 mm, and the mixing time is 3 minutes.

[0039] Embodiment 11 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (3), the extrusion speed of the extruder is 5 r / min, and the extrusion port temperature of the extruder is 120°C.

[0040] Example 12 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (3), the extrusion speed of the extruder is 12 r / min, and the extrusion port temperature of the extruder is 140°C.

[0041] Embodiment 13 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (4), a drying oven with a temperature of 275° C. and a time of 5 minutes is used during the vulcanization process.

[0042] Embodiment 14 A method for preparing a contraceptive implant core, which is different from that of Example 1 in that, in step (4), a drying oven with a temperature of 285° C. and a curing time of 2 minutes is used during the vulcanization process.

[0043] Comparative Example Comparative Example 1 A method for preparing a contraceptive implant core, which is different from Example 1 in that methylbutynol is not used in Group A components.

[0044] Comparative Example 2 A method for preparing a contraceptive implant core, which is different from Example 1 in that no mixing auxiliary agent is used in the group B components.

[0045] Comparative Example 3 A method for preparing a contraceptive implant core, which is different from Example 1 in that methylbutynol is not used in Group A components and no mixing auxiliary agent is used in Group B components.

[0046] Comparative Example 4 A method for preparing a contraceptive implant core, which is different from Example 1 in that microcrystalline cellulose is not used in the mixing auxiliary agent.

[0047] Comparative Example 5 A method for preparing a contraceptive implant core, which is different from Example 1 in that magnesium stearate is not used in the mixing auxiliary agent.

[0048] Performance testing (1) Calculation of yield rate: yield rate = (number of qualified products / total production quantity) × 100%; (2) Calculation of raw material loss rate, raw material loss rate = (total mass of raw materials - total mass of produced drug core) / total mass of raw materials × 100%; The preparation methods of contraceptive implant drug cores in Examples 1-14 and Comparative Examples 1-5 were respectively tested for application, and the yield and raw material loss rates calculated as above were recorded in Table 1 accordingly.

[0049] Table 1 Application test results of Examples 1-14 and Comparative Examples 1-5 It can be seen from Example 1 and Comparative Examples 1-3 in combination with Table 1 that the use of methylbutynol in Group A and the use of a mixed auxiliary agent comprising microcrystalline cellulose and magnesium stearate in Group B can significantly improve the yield rate and significantly reduce the raw material loss rate, and the two have a synergistic effect. The use of methylbutynol or a mixed auxiliary agent alone has limited corresponding effects, especially in terms of the improvement of the yield rate and the reduction of the raw material loss rate, which is far less than the excellent effect brought by the combined effect of the two. Combined with Comparative Examples 4-5 and Table 1, it can be seen that if any one of microcrystalline cellulose and magnesium stearate is used alone as a mixed auxiliary agent, not only will the effect brought by the mixed auxiliary agent itself be greatly discounted, but also the synergistic effect brought by the combination of the mixed auxiliary agent and methylbutynol will be significantly reduced. It can be seen that microcrystalline cellulose and magnesium stearate not only have a composite synergistic effect, but also ensure that the combination of the mixed auxiliary agent and methylbutynol brings a necessary condition for outstanding progressive effects.

[0050] It can be seen from Example 1 and Comparative Examples 2-4 and Table 1 that when the weight ratio of microcrystalline cellulose to magnesium stearate is (8-15): 1, the mixing auxiliary agent can be guaranteed to exert an excellent and stable application effect. Among them, when the weight ratio of microcrystalline cellulose to magnesium stearate is 12: 1, the yield and raw material loss rate obtained by the above test are better.

[0051] Combining Example 1 and Comparative Examples 5-6 with Table 1, it can be seen that when the mass proportion of methylbutynol in Group A components is 0.5-1%, it can exert excellent corresponding effects during the application process; Combining Example 1 and Comparative Examples 7-8 with Table 1, it can be seen that when the mass proportion of the mixing auxiliary agent in Group B components is 3-5%, it can exert excellent corresponding effects during the application process; and the selection of the above-mentioned dosage range can ensure a stable and better yield and raw material loss rate.

[0052] Combining Example 1 and Comparative Examples 9-14 and Table 1, it can be seen that the distance between the rollers during mixing is 0.1-0.2 mm, and the mixing time is 2-3 min; the extrusion speed of the extruder is 5-12 r / min, and the extrusion port temperature of the extruder is 120-140° C.; the drying oven with a temperature of 275-285° C. and a time of 2-5 min are used during the vulcanization process; all of these can ensure that the components of Group A and Group B are fully mixed, and that the methylbutynol and mixing aids contained therein can also fully play their role, thereby obtaining a better extrusion morphology, ensuring the stable and excellent application of the contraceptive implant core preparation method, and thus the performance of the yield and raw material loss rate are stable and better.

[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a contraceptive implant core, characterized in that: The steps include: (1) Weigh the components of Group A and Group B and pre-mix them separately; (2) Mixing the components of group A and group B to obtain a mixed rubber; (3) placing the rubber mixture in an extruder and extruding the mixture through a screw to obtain an extruded core rod; (4) The extruded core rod is vulcanized, cut, cooled, and trimmed to obtain a finished core; The group A components include the following raw materials: levonorgestrel, LS-4100 silicone rubber, white carbon black, platinum complex, methyl butynol; The group B components include the following raw materials: levonorgestrel, LS-4100 silicone rubber, white carbon black, hydrogen-containing silicone oil, and mixing aids; The mixing aid is composed of raw materials including microcrystalline cellulose and magnesium stearate, and the weight ratio of microcrystalline cellulose to magnesium stearate is (8-15):

1.

2. The method for preparing the contraceptive implant core according to claim 1, characterized in that: The weight ratio of the microcrystalline cellulose to magnesium stearate is 12:

1.

3. The method for preparing the contraceptive implant core according to claim 1, characterized in that: The mass proportion of the methylbutynol in the Group A components is 0.5-1%.

4. The method for preparing the contraceptive implant core according to claim 1, characterized in that: The mass proportion of the mixing auxiliary agent in the components of Group B is 3-5%.

5. The method for preparing the contraceptive implant core according to claim 1, characterized in that: In step (2), the distance between the rollers during mixing is 0.1-0.2 mm, and the mixing time is 2-3 min.

6. The method for preparing the contraceptive implant core according to claim 1, characterized in that: In step (3), the extrusion speed of the extruder is 5-12 r / min, and the extrusion port temperature of the extruder is 120-140°C.

7. The method for preparing the contraceptive implant core according to claim 1, characterized in that: In step (4), a drying oven with a temperature of 275-285° C. and a curing time of 2-5 min is used during the vulcanization process.

8. The method for preparing the contraceptive implant core according to claim 1, characterized in that: In step (4), the finished drug core has a length of 43 mm, a diameter of 2.1±0.01 mm, and a weight of 145-157 mg.

9. The method for preparing the contraceptive implant core according to claim 1, characterized in that: The weight ratio of the group A components to the group B components is 1:1.

Citation Information

Patent Citations

  • Preparation method of contraceptive implant medicine core

    CN113413358A